Review on distribution of endo-parasites of fish in Ethiopia - Hailekiros Gebreegziabher Gebremedhn; Assefa Kebede Tsegay (Parasite Epidemiology and Control, 2017)
Recently the government of Ethiopia paid great attention to livestock and fish production sectors of the country. As evidence, the sector is organized in the form of ministry, Ethiopian Ministry of Livestock and Fisheries. This is great progress in the history of the country. These and other focuses given to the sector are expected to dramatically change the eating habit of the community towards fish meat as well as fish production trends of the country. However; parasitic diseases of fish are great challenges in the processes of fish production in Ethiopia and hence, the primary goal of this paper is to compile all available information concerning distribution of endo-parasites of fish in the country and provide the necessary information for policy makers, investors and researchers interested in the field. In line with the objective of this paper, there are many reports on helminth endo-parasites of fish in Ethiopia reported by different authors with different prevalence's from different corners of the country. Digenean trematodes, nematodes and cestodes are the major endo-parasites reported from the different water bodies of the country. To mention some of the major species of parasites affecting different species of fish are: Clinostomum and Euclinostomum species of trematodes, Contracaecum and Eustrongylides species of nematodes and Ligula intestinalis and Proteocephalus species of cestodes mainly affecting: Clarias gariepinus, Oreochromis niloticus, Barbus and Cyprinus carpio species of fish. Most reports showed that fish Endo-parasite are more prevalent in Ethiopia in Lake Awassa, Lake Lugo (Hayke) and Lake Tana. In conclusion, endo-parasites of fish are highly prevalent in different water bodies of Ethiopia. Therefore, there should be a nationwide strategy in prevention and control of endo-parasites of fish, and further study on the economic and public health impact of these parasites should be studied.